PHYTOTOXICITY OF LIMONENE AGAINST AMARANTHUS VIRIDIS L. - SUPRIYA VAID; DAIZY R. BATISH; H. P. SINGH; R. K. KOHLI (The Bioscan, 2011)
A study was undertaken to assess the phytotoxic / allelopathic effect of limonene, a volatile monoterpene against the weed – Amaranthus viridis L. The germination of the weed was significantly inhibited even at very low concentrations (0.1 and 0.5 μL) of limonene where about 4 and 11% inhibition were observed respectively. Not only germination, but the seeding growth of the test weed in terms of radicle length, seedling length and seedling dry weight were appreciably reduced in response to limonene. At the concentration of 0.7 μL, the seedling length was reduced by about 25% while seedling dry weight was reduced by about 9%. Similarly, there was a significant reduction in the chlorophyll content and respiratory activity of the test weed which were reduced by over 50% upon treatment with 0.7 μL limonene. On the basis of this study, it is concluded that limonene has a weed suppressing potential and therefore, can be used for future weed management programmes either directly or by serving as a lead molecule.